Radiolytic alteration of biopolymers in the Mulga Rock (Australia) uranium deposit - Jaraula, Caroline; Schwark, Lorenz; Moreau, X.; Pickel, W.; Bagas, L.; Grice, Kliti (Pergamon, 2014)
We investigated the effect of ionizing radiation on organic matter (OM) in the carbonaceous uranium (U) mineralization at the Mulga Rock deposit, Western Australia. Samples were collected from mineralized layers between 53 and 58.5 m depths in the Ambassador prospect, containing <5300 ppm U. Uranium bears a close spatial relationship with OM, mostly finely interspersed in the attrinite matrix and via enrichments within liptinitic phytoclasts (mainly sporinite and liptodetrinite). Geochemical analyses were conducted to: (i) identify the natural sources of molecular markers, (ii) recognize relationships between molecular markers and U concentrations and (iii) detect radiolysis effects on molecular marker distributions. Carbon to nitrogen ratios between 82 and 153, and Rock–Eval pyrolysis yields of 316–577 mg hydrocarbon/g TOC (HI) and 70–102 mg CO2/g TOC (OI) indicate a predominantly lipid-rich terrigenous plant OM source deposited in a complex shallow swampy wetland or lacustrine environment. Saturated hydrocarbon and ketone fractions reveal molecular distributions co-varying with U concentration. In samples with <1700 ppm U concentrations, long-chain n-alkanes and alkanones (C27–C31) reveal an odd/even carbon preference indicative of extant lipids.Samples with ⩾1700 ppm concentrations contain intermediate-length n-alkanes and alkanones, bearing a keto-group in position 2–10, with no carbon number preference. Such changes in molecular distributions are inconsistent with diagenetic degradation of terrigenous OM in oxic depositional environments and cannot be associated with thermal breakdown due to the relatively low thermal maturity of the deposits (Rr = 0.26%). It is assumed that the intimate spatial association of high U concentrations resulted in breakdown via radiolytic cracking of recalcitrant polyaliphatic macromolecules (spores, pollen, cuticles, or algal cysts) yielding medium chain length n-alkanes (C13–C24). Reactions of n-alkenes with OH− radicals from water hydrolysis produced alcohols that dehydrogenated to alkanones or through carbonylation formed alkanones. Rapid reactions with hydroxyl radicals likely decreased the isomerization of n-alkenes and decreased alkanone diversity, such that the alkan-2-one isomer is predominant. This specific distribution of components generated by natural radiolysis enables their application as “radiolytic molecular markers”. Breaking of C–C bonds through radiolytic cracking at temperatures much lower than the oil window (<50 °C) can have profound implications on initiation of petroleum formation, paleoenvironmental reconstructions, mineral exploration and in tracking radiolysis of OM.